2014
DOI: 10.1109/tvcg.2014.2346298
|View full text |Cite
|
Sign up to set email alerts
|

Error Bars Considered Harmful: Exploring Alternate Encodings for Mean and Error

Abstract: When making an inference or comparison with uncertain, noisy, or incomplete data, measurement error and confidence intervals can be as important for judgment as the actual mean values of different groups. These often misunderstood statistical quantities are frequently represented by bar charts with error bars. This paper investigates drawbacks with this standard encoding, and considers a set of alternatives designed to more effectively communicate the implications of mean and error data to a general audience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
240
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(245 citation statements)
references
References 38 publications
5
240
0
Order By: Relevance
“…HCI and infovis researchers also have the exciting opportunity to contribute new research, for example by studying new visual representations for communicating study results (Correll and Gleicher, 2014;Perin et al, 2014). Such representations do not have to be static, and there are many ways computers, animation, and interactivity can be used to teach statistics and convey scientific evidence to a wide audience (Victor, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HCI and infovis researchers also have the exciting opportunity to contribute new research, for example by studying new visual representations for communicating study results (Correll and Gleicher, 2014;Perin et al, 2014). Such representations do not have to be static, and there are many ways computers, animation, and interactivity can be used to teach statistics and convey scientific evidence to a wide audience (Victor, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The scarcity of graphical standards should be taken as an opportunity to explore custom visual designs, within the limits suggested by Tip 18. For example, there are many options for displaying error bars (Figure 9): while the design (1) is widely used, (2) is a common alternative that has the advantage of de-emphasizing confidence limits; The variant (3) improves the legibility of point estimates; Error bars can also be combined with bar charts (4); Bars help compare magnitudes on a ratio scale (Zacks and Tversky, 1999), but they introduce visual asymmetry (Newman and Scholl, 2012;Correll and Gleicher, 2014) and tend to de-emphasize error bars; This is evident in the so-called "dynamite plots" (5); The design (6) supports ratio comparison while maintaining emphasis on error bars; Finally, error bars can be combined with line charts (7) to convey temporal ordering (Zacks and Tversky, 1999) or within-subject factors (Cumming, 2012, p.172). Fig.…”
Section: Plotting Confidence Intervalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Olston et al [8] examined visualizations for presenting bounded uncertainty by adjusting the visual elements and including transparency in the visualizations and Tak et al [13] used seven variations of a line graph to investigate the perceived certainty. Correll and Gleicher [1] proposed a redesign of bar charts and found that less well-known visualizations improve performance for interferential tasks.…”
Section: Related Workmentioning
confidence: 99%
“…An additional benefit is that participants of crowdsourced user studies can participate at any given time, and is not limited to the opening hours of the lab. While there has not yet been any work published where crowdsourcing has been utilized for evaluating scientific visualization research, crowdsourcing has been successfully utilized for user studies in information visualization [9,10,16,17,19,24,38,47].…”
Section: Introductionmentioning
confidence: 99%